The value relevance of intangible non-current assets during different economic conditions and accounting environments / Zaleha Abdul Shukor, Muhd Kamil Ibrahim, Jagjit Kaur, Hamezah Md Nor - Abdul Shukor, Zaleha; Ibrahim, Muhd Kamil; Kaur, Jagjit (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
The issue of value relevance of intangible non-current assets (NCA) is important in the financial reporting literature due to the ever increasing interest in the components of intangible assets items including goodwill and intellectual capital. This study examines the value relevance of reported intangible NCA among firms listed on the main board of Bursa Malaysia throughout a 12-year period from 1990 until 2001. During this time period, Malaysia went through three different economic and accounting environmental conditions. Early 1990s saw an excellent economic condition but with less stringent accounting regulatory period. However, 1997 and 1998 were the financial crisis period. In 1997, the Malaysian Accounting Standards Board (MASB) was established by the Malaysia government. From 1999 until 2001, Malaysia went through a recovery economic period plus a more stringent accounting regulatory framework. Based on the value relevance model, we find evidence that intangible NCA continuously show a negative association with firms’ share market price throughout the three different economic periods and accounting environments among our sample firms. However, as expected the association was not significant before the establishment of MASB compared to after. Our finding is consistent with extant studies on the issue of value relevance of intangible NCA during poor economic condition. However, our finding is not consistent with prior studies concerning value relevance of intangible assets during stable economic condition. Nevertheless, our finding is consistent with the on-going argument and theory of capitalized intangible assets more likely to reflect uncertain expected future cash flows, hence value relevance is perceived by investors to be biased.